The CD6 interactome orchestrates ligand-independent T cell inhibitory signaling - Santos, RF; de Sousa Linhares, A; Steinberger, P; Davis, SJ; Oliveira, L; Carmo, AM (BioMed Central, 2024)
Background: T-cell membrane scaffold proteins are pivotal in T cell function, acting as versatile signaling hubs. While CD6 forms a large intracellular signalosome, it is distinguished from typical scaffolds like LAT or PAG by possessing a substantial ectodomain that binds CD166, a well-characterized ligand expressed on most antigen-presenting cells (APC), through the third domain (d3) of the extracellular region. Although the intact form of CD6 is the most abundant in T cells, an isoform lacking d3 (CD6∆d3) is transiently expressed on activated T cells. Still, the precise character of the signaling transduced by CD6, whether costimulatory or inhibitory, and the influence of its ectodomain on these activities are unclear. Methods: We expressed CD6 variants with extracellular deletions or cytosolic mutations in Jurkat cells containing eGFP reporters for NF-κB and NF-AT transcription factor activation. Cell activation was assessed by eGFP flow cytometry following Jurkat cell engagement with superantigen-presenting Raji cells. Using imaging flow cytometry, we evaluated the impact of the CD6-CD166 pair on cell adhesiveness during the antigen-dependent and -independent priming of T cells. We also examined the role of extracellular or cytosolic sequences on CD6 translocation to the immunological synapse, using immunofluorescence-based imaging. Results: Our investigation dissecting the functions of the extracellular and cytosolic regions of CD6 revealed that CD6 was trafficked to the immunological synapse and exerted tonic inhibition wholly dependent on its cytosolic tail. Surprisingly, however, translocation to the synapse occurred independently of the extracellular d3 and of engagement to CD166. On the other hand, CD6 binding to CD166 significantly increased T cell:APC adhesion. However, this activity was most evident in the absence of APC priming with superantigen, and thus, in the absence of TCR engagement. Conclusions: Our study identifies CD6 as a novel ‘on/off’ scaffold-receptor capable of modulating responsiveness in two ways. Firstly, and independently of ligand binding, it establishes signaling thresholds through tonic inhibition, functioning as a membrane-bound scaffold. Secondly, CD6 has the capacity for alternative splicing-dependent variable ligand engagement, modulating its checkpoint-like activity.